Development and characterization of modified silicone – dammar coating resin / Rosnah Zakaria - Zakaria, Rosnah (Institute of Graduate Studies, UiTM, 2014)
The purpose of this study is to develop and characterized the new modified silicone binder resin. The silicone, synthetic resin bought from Dow Corning Corp. and dammar bought from local supplier. Ten (10) samples were prepared and one of them was silicone resin without dammar. The samples were designated as SD0, SD5, SD10, SD15, SD20, SD25, SD30, SD35, SD40 and SD45. The mixture was coat onto aluminum q-panel using spin coater and left in room temperature for around 7 – 8 days for curing process. The cured samples were undergone the mechanical and electrochemical characteristic. The mechanical characterizations include viscosity, cross-hatch test, pull off test, wetting and impact test. Results for cross hatch test showed that 5-15 wt% of dammar in the silicone resin provide the better adhesion on aluminum q-panel with the edges of the cut are smooth and none of the square lattice detached. In the impact test, no fracture can be observed on the impact surfaces when the 1 kg load was released on SD0 – SD20 dried coating surfaces.